Interweaving Religious Dialogue: Dynamics and Conflict Resolution Between Islam and Judaism - Hermawan, Ucep; Muhlas, Muhlas (Jurnal Iman dan Spiritualitas, 2025)
The purpose of this research is to explore the dynamics of Islamic-Jewish dialogue and the conflict resolution efforts undertaken between these two religions. This study employs a qualitative approach, utilizing a literature review method to collect and analyze data from various sources. The findings reveal several key points: first, the conflict between Islam and Judaism is often identified with the Israel-Palestine conflict, which represents a significant international issue. Second, Islamic-Jewish dialogue remains limited, with notable efforts emerging only in recent years, such as those led by Imam Shamsi Ali (Islam) and Rabbi Marc (Judaism) in the United States. These dialogues aim to foster mutual understanding by emphasizing that all religions fundamentally strive for human salvation, while acts of violence in the name of religion stem from individual actions rather than representing religious institutions. This study contributes to the discourse on interfaith dialogue by highlighting the potential of Islamic-Jewish dialogue as a tool for conflict resolution and promoting peace.